2015
DOI: 10.6061/clinics/2015(03)04
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life of adolescents with type 1 diabetes

Abstract: INTRODUCTION:Diabetes mellitus is a highly prevalent chronic disease. Type 1 diabetes mellitus usually develops during infancy and adolescence and may affect the quality of life of adolescents.OBJECTIVE:To evaluate the quality of life of adolescents with type 1 diabetes mellitus in a metropolitan region of western central Brazil.METHODS:Adolescents aged 10–19 years who had been diagnosed with type 1 diabetes mellitus at least 1 year previously were included. Patients with verbal communication difficulties, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
5
18
1
8
Order By: Relevance
“…When comparing the QOL of children and their parents with a chronic disease, it was revealed that the scores of QOL by parents are estimated lower on all scales of the questionnaire, except for social functioning (10). Adolescents are more resistant to accepting the disease than younger children because they no longer depend on their parents or guardians for care and are responsible for their own health (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the QOL of children and their parents with a chronic disease, it was revealed that the scores of QOL by parents are estimated lower on all scales of the questionnaire, except for social functioning (10). Adolescents are more resistant to accepting the disease than younger children because they no longer depend on their parents or guardians for care and are responsible for their own health (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The participants wanted young people to know that it was OK to be angry and upset, but that they could do what they wanted to do with few limitations. Although quality of life is a frequent focus of type 1 diabetes research ( 32 34 ), no studies have addressed the importance of children and adolescents with type 1 diabetes learning that they can still do the things they had previously planned on doing in life. Participants emphasized how important it is for parents and HCPs to demonstrate a positive attitude about type 1 diabetes and avoid comments that may validate young people’s belief that the life they knew is over because of their diagnosis.…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%
“…It is a genetic-based autoimmune condition resulting from absolute insulin deficiency due to immune-mediated destruction of pancreatic β cells [1]. …”
Section: Introductionmentioning
confidence: 99%